Manipulating Picosecond Photoresponse in van der Waals Heterostructure Photodetectors. (6th May 2022) - Zeng, Zhouxiaosong; Ge, Cuihuan; Braun, Kai; Eberle, Martin; Wang, Yufan; Zheng, Biyuan; Zhu, Chenguang; Sun, Xingxia; Huang, Lanyu; Luo, Ziyu; Chen, Ying; Duan, Huigao; et al.
Abstract: Self‐powered ultrafast 2D photodetectors have demonstrated great potential in imaging, sensing, and communication. Understanding the intrinsic ultrafast charge carrier generation and separation processes is essential for achieving high‐performance devices. However, probing and manipulating the ultrafast photoresponse is limited either by the temporal resolution of the conventional methods or the required sophisticated device configurations. Here, van der Waals heterostructure photodetectors are constructed based on MoS2 /WSe2 p–n and n–n junctions and manipulate the picosecond photoresponse by combining photovoltaic (PV) and photothermoelectric (PTE) effects. Taking time‐resolved photocurrent (TRPC) measurements, a TRPC peak at zero time delay is observed with decay time down to 4 ps in the n–n junction device, in contrast to the TRPC dip in the p–n junction and pure WSe2 devices, indicating an opposite current polarity between PV and PTE. More importantly, with an ultrafast photocurrent modulation, a transition from a TRPC peak to a TRPC dip is realized, and detailed carrier transport dynamics are analyzed. This study provides a deeper understanding of the ultrafast photocurrent generation mechanism in van der Waals heterostructures and offers a new perspective in instruction for designing more efficient self‐powered photodetectors. Abstract : Comprehensive understanding of interaction between photovoltaic and photothermoelectric effects is demonstrated via a time‐resolved photocurrent (TRPC) measurement technique. Compared to MoS2 /multilayer WSe2 p–n junction having a conventional TRPC dip, MoS2 /1L WSe2 n–n junction processes a distinct TRPC peak, which is attributed to the opposite polarity between photovoltaic and photothermoelectric currents and can be further modulated via an external bias.